The spectrum of cutaneous adverse events during encorafenib and binimetinib treatment in B‐rapidly accelerated fibrosarcoma‐mutated advanced melanoma. (13th December 2018) - Graf, N.P.; Koelblinger, P.; Galliker, N.; Conrad, S.; Barysch, M.; Mangana, J.; Dummer, R.; Cheng, P.F.; Goldinger, S.M.
Abstract: Background: B‐rapidly accelerated fibrosarcoma (BRAF) inhibitor encorafenib alone and in combination with MEK inhibitor binimetinib improves survival in BRAF‐mutated melanoma patients. So far, the range of cutaneous adverse events has been characterized only for established BRAF inhibitors (vemurafenib, dabrafenib) and MEK inhibitors (trametinib, cobimetinib). Objective: The aim of this study was to investigate cutaneous adverse events emerging in melanoma patients treated with encorafenib and binimetinib. Methods: Patients treated with BRAF and MEK inhibitors in clinical trials at the University Hospital of Zurich were identified. Frequency and features of cutaneous adverse events as well as their management were assessed based on the prospectively collected clinical and histopathological data. The events emerging during encorafenib and/or binimetinib therapy were compared to other BRAF and MEK inhibitors at the institution and in the literature. Results: The most frequent cutaneous adverse events observed in patients treated with encorafenib alone ( n  = 24) were palmoplantar hyperkeratosis (54%), palmoplantar erythrodysesthesia (58%) and alopecia (46%). Drug‐induced papulopustular eruptions prevailed in patients with binimetinib monotherapy ( n  = 25). The most frequent cutaneous adverse events in patients treated with encorafenib/binimetinib ( n  = 49) were palmoplantar hyperkeratosis (10%). Conclusion: Compared to data published for established BRAFi, encorafenib monotherapy showed less hyperproliferative cutaneous adverse events. In contrast, palmoplantar hyperkeratosis and palmoplantar erythrodysesthesia seem to occur more often. The combination of encorafenib and binimetinib is well tolerated and induces few cutaneous adverse events. Abstract : Linked article: This article is commented on E. Livingstone, pp. 630–631 in this issue. To view this article visithttps://doi.org/10.1111/jdv.15527 .